The influence of legibility on attachment towards the shopping streets of Kuala Lumpur - Ujang, Norsidah; Shamsudin, Shuhana (Universiti Putra Malaysia Press, 2012)
Research on urban design mainly focuses on legibility of places generated by the physical and visual images, and thus only a few emphasize on its relationship with the psychological sense of place. This study examined legibility and its influence on users’ attachment to the shopping places in Kuala Lumpur city centre, Malaysia. The places comprised of the main shopping streets of Jalan Tuanku Abdul Rahman, Jalan Masjid India, Jalan Petaling and Jalan Bukit Bintang. Questionnaire surveys and face-to-face interviews were conducted to identify the respondents’ perception of legible elements within the areas. The analysis was supported by evidence gathered from direct observations of the streets’ setting and activities. The findings demonstrated that the legibility of the streets is strongly associated with the users’ functional attachment, dependence and familiarity with the streets’ activities. It is supported by the identifiable activity nodes which make the places vibrant. In contrast, the influence of the physical forms and characteristics on the attachment does not reflect the same level of significance. Improvement of the streetscape and preservation of distinctive features such as old building facade will make places more legible. The findings inform planners and designers of the importance of users’ attachment and recognition of meaningful places in managing changes in the physical environment. The ability of places to support diverse activities will reinforce place attachment particularly in the changing context of multi-cultural city of Kuala Lumpur.